Kejadian Pertusis di Kelurahan Jatingaleh, Kecamatan Candisari, Kota Semarang Tahun 2024 - Tristanti, Wita Istiqomah; Muh, Fauzi; Adi, Mateus Sakundarno; Martini, Martini; Suhartono, Suhartono (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Pertussis is a respiratory disease caused by the bacteria Bordetella pertussis. In Semarang City, from 2022-2023, no cases of pertussis were found. On June 18, 2024, the Semarang City Health Office received a report of 2 pertussis suspects from the primary health center with complaints of coughing for two weeks accompanied by vomiting, and a